Remyelination Pharmacotherapy Investigations Highlight Diverse Mechanisms Underlying Multiple Sclerosis Progression - Melchor, George S. (ACS Pharmacol Transl Sci, 2019)
[Image: see text] Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system characterized by a complex lesion microenvironment. Although much progress has been made in developing immunomodulatory treatments to reduce myelin damage and delay the progression of MS, there is a paucity in treatment options that address the multiple pathophysiological aspects of the disease. Currently available immune-centered therapies are able to reduce the immune-mediated damage exhibited in MS patients, however, they cannot rescue the eventual failure of remyelination or permanent neuronal damage that occurs as MS progresses. Recent advances have provided a better understanding of remyelination processes, specifically oligodendrocyte lineage cell progression following demyelination. Further there have been new findings highlighting various components of the lesion microenvironment that contribute to myelin repair and restored axonal health. In this review we discuss the complexities of myelin repair following immune-mediated damage in the CNS, the contribution of animal models of MS in providing insight on OL progression and myelin repair, and current and potential remyelination-centered therapeutic targets. As remyelination therapies continue to progress into clinical trials, we consider a dual approach targeting the inflammatory microenvironment and intrinsic remyelination mechanisms to be optimal in aiding MS patients.